The Effect of Competence, Motivation, and Work Discipline on the Performance of Employees at Perumda Air Minum Tirta Raharja in Bandung Regency - Rizal Permana; Palupi Permata Rahmi; Widyastuti Nurmalia Utami (International Journal of Marketing & Human Resource Research, 2026)
This study aims to analyze the effects of competence, work motivation, and work discipline on employee performance at Perumda Air Minum Tirta Raharja in Bandung Regency. This study employs a quantitative method with a descriptive and verificatory approach, aiming to describe the conditions of the research variables and empirically test the relationships among them. The research data were obtained by distributing questionnaires to 78 employees who were selected as research respondents. The collected data were analyzed using multiple linear regression. The results showed that competence did not have a significant effect on employee performance. The NJI results indicated that competence was rated good (44.81), motivation was rated good (43.83), work discipline was rated good (59.31), and employee performance was rated good (52.32). In part, competence has no effect (0.217 > 0.05), indicating that differences in competence levels among employees do not yet yield meaningful changes in performance. while motivation (0.009 < 0.05) and work discipline (0.000 < 0.05) affect performance, meaning that work motivation and work discipline are proven to have a positive and significant effect on employee performance. Simultaneously, competence, work motivation, and work discipline have a significant effect on employee performance, with an R-squared of 70.4%, indicating that these three variables account for most of the variation in employee performance. The findings of this study confirm that improving employee performance in the public service sector needs to focus on strengthening motivation and work discipline, supported by continuous competence development to improve the quality of service to the community